1996
DOI: 10.1164/ajrccm.153.2.8564109
|View full text |Cite
|
Sign up to set email alerts
|

Airflow limitation in chronic bronchitis is associated with T-lymphocyte and macrophage infiltration of the bronchial mucosa.

Abstract: To investigate whether the airway inflammatory process is different in patients with chronic bronchitis with airflow limitation and those with chronic bronchitis without airflow limitation, we obtained bronchial biopsies from 14 subjects with chronic sputum production and fixed airway obstruction, and from 10 subjects with chronic sputum production and normal FEV1, all with a history of cigarette smoking. Paraffin-embedded and frozen bronchial biopsies were examined by immunohistochemistry to identify the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
109
1
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 18 publications
10
109
1
7
Order By: Relevance
“…The absence of any correlation between the number of neutrophils infiltrating the large airway subepithelium and increasing obstruction is consistent with previous studies which have reported no increase in neutrophils in the large [4,5,8,11] or the small airways [15,24] in subjects with COPD. The discordance of these results with those showing an increase in numbers of neutrophils and markers of neutrophil activation in bronchoalveolar lavage [10,11,13,14,25], induced sputum [26±28] and airway epithelium [29] remains to be explained.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of any correlation between the number of neutrophils infiltrating the large airway subepithelium and increasing obstruction is consistent with previous studies which have reported no increase in neutrophils in the large [4,5,8,11] or the small airways [15,24] in subjects with COPD. The discordance of these results with those showing an increase in numbers of neutrophils and markers of neutrophil activation in bronchoalveolar lavage [10,11,13,14,25], induced sputum [26±28] and airway epithelium [29] remains to be explained.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated an increase in the number of T-cells infiltrating the large airway subepithelium and a shift towards a CD8 phenotype [3±8] in addition to increases in the number of macrophages [4,5,8]. An increase in the number of infiltrating eosinophils has been observed in the large airway subepithelium although they do not appear to be degranulated as in asthma [9].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…6 Although the biologic mechanisms of COPD exacerbation are still not fully understood, some evidence suggests that an activation of first-line defense (airway epithelial cells and alveolar macrophages) releases chemotactic factors by bacterial/viral pathogens or noninfectious triggered stimuli 7 and leads to the recruitment of neutrophils, with the secretion of a wide range of pro-inflammatory cytokines, thereby causing a further amplification of systemic and local processes. 8,9 Change in inflammatory biomarker levels from a steady state may define COPD exacerbation onset, clinical course, severity, and prognosis of hospitalized patients. 10,11 Inhaled corticosteroids are potent anti-inflammatory nonspecific medications that can modulate the systemic immune response of stable COPD patients, 12 but their role in the efficacy of treatment remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, macrophages, and CD8 ϩ T cells have been implicated in COPD pathogenesis in a number of studies. [1][2][3][4][5][6] More recently, airway infiltration by CD4 T cells and B cells has also been shown to associate with the progression of COPD. 7,8 This cellular inflammation is associated with airway remodeling and destruction, but it is not clear which cell types are responsible for the damage.…”
mentioning
confidence: 99%